2016
DOI: 10.1371/journal.pone.0160600
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Lactating Dairy Cows to Acute Pre-Ovulatory Heat Stress Affects Granulosa Cell-Specific Gene Expression Profiles in Dominant Follicles

Abstract: High environmental temperatures induce detrimental effects on various reproductive processes in cattle. According to the predicted global warming the number of days with unfavorable ambient temperatures will further increase. The objective of this study was to investigate effects of acute heat stress during the late pre-ovulatory phase on morphological, physiological and molecular parameters of dominant follicles in cycling cows during lactation. Eight German Holstein cows in established lactation were exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Follicular E2 was much higher in winter than in summer [20]. Other study stated no differences were observed in follicular E2 concentrations between heat-stress and non heat-stressed cows [12]. Heat-stressed cows with lowered E2 during the second half of their cycle [21] or during their entire estrous cycle [11] exhibited reduced pre-ovulatory surges of E2.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Follicular E2 was much higher in winter than in summer [20]. Other study stated no differences were observed in follicular E2 concentrations between heat-stress and non heat-stressed cows [12]. Heat-stressed cows with lowered E2 during the second half of their cycle [21] or during their entire estrous cycle [11] exhibited reduced pre-ovulatory surges of E2.…”
Section: Introductionmentioning
confidence: 87%
“…The number of follicles and their functions are affected by HS. Heat stress compromises follicular growth [11] and alters gene expression profiles in the granulosa cells of large pre-ovulatory follicles, which can affect follicular growth [12]. Follicles and oocytes have been damaged by HS, and cows needed 2 -3 estrous cycles to recover from HS effects [13].…”
Section: Introductionmentioning
confidence: 99%
“…All procedures were approved by the ethics committee of the state government in Mecklenburg-West Pomerania, Germany (LALLF M-V/TSD/7221.3-1.1-074/12), and the data described herein are part of a recently published study (Vanselow et al, 2016). More specifically, 10 German Holstein dairy cows in established second lactation (192 ± 20 DIM) were kept under the same normal environmental conditions in a freestall barn at the Leibniz Institute for Farm Animal Biology (FBN) with daily ad libitum feeding.…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…Heat stress also contributes to reduced reproductive efficiency by limiting reproductive estrus expression/detection and decreasing conception rate [5]. There are decreases in estradiol-17β concentrations in heat stressed cows, and these reductions in estradiol limit estrus behavior [101,102,106,107]. Fescue toxicosis is another environmental factor that causes infertility in cattle.…”
Section: Physiological and Environmental Contributors To Pregnancy Lomentioning
confidence: 99%